2007
DOI: 10.1111/j.1365-294x.2007.03584.x
|View full text |Cite
|
Sign up to set email alerts
|

Density‐related changes in selection pattern for major histocompatibility complex genes in fluctuating populations of voles

Abstract: Host-pathogen interactions are of particular interest in studies of the interplay between population dynamics and natural selection. The major histocompatibility complex (MHC) genes of demographically fluctuating species are highly suitable markers for such studies, because they are involved in initiating the immune response against pathogens and display a high level of adaptive genetic variation. We investigated whether two MHC class II genes (DQA1, DRB) were subjected to contemporary selection during increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 77 publications
7
80
2
2
Order By: Relevance
“…This has led to the hope that studying a single MHC gene will reveal patterns of evolution representative of the MHC as a whole. Based on this assumption, most studies are restricted to only one MHC gene (see exceptions, for example, in Edwards et al, 1997;Sommer, 2003;Bryja et al, 2007;Tollenaere et al, 2008;Babik et al, 2008.). However, there are at least two reasons for analysing more MHC genes.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the hope that studying a single MHC gene will reveal patterns of evolution representative of the MHC as a whole. Based on this assumption, most studies are restricted to only one MHC gene (see exceptions, for example, in Edwards et al, 1997;Sommer, 2003;Bryja et al, 2007;Tollenaere et al, 2008;Babik et al, 2008.). However, there are at least two reasons for analysing more MHC genes.…”
Section: Introductionmentioning
confidence: 99%
“…The MHC often displays considerable differentiation across geographical landscapes as has been found in populations of mammals, birds, and fishes (for example, Landry and Bernatchez, 2001;Miller et al, 2001;Wegner et al, 2003;Bryja et al, 2007;Dionne et al, 2007;Ekblom et al, 2007). Population subdivision at the MHC may arise because of mutation, gene flow, genetic drift, or local adaptation (Schierup et al, 2000).…”
mentioning
confidence: 99%
“…In contrast, Kruiswijk et al (2005) found a complete divergence in class II, but not in class I of a barbs species flock. Differences in evolutionary rates and the response to selection between both genes have been observed not only in fish but also in mammals and birds (Go et al, 2003;Bryja et al, 2007). Class I and class II molecules differ in the nature of the peptides that they bind, in how they bind and process them (Castellino et al, 1997;Kaufman et al, 1999;Grommé and Neefjes, 2002;Go et al, 2003) and in the T cells they react with (Housset and Malissen, 2003;Huseby et al, 2003).…”
Section: Differences Between Mh-linked Markersmentioning
confidence: 99%
“…In comparison to studies of geographic patterns in MHC variation, there have been relatively few studies on MHC which also include a temporal dimension, despite the possibility that selective forces across time within a population may differ from those across populations (Smulders et al, 2003;Sommer, 2003;Beacham et al, 2004;Seddon and Ellegren, 2004;Westerdahl et al, 2004;Coughlan et al, 2006;Oliver et al, 2009). Moreover, most studies focus on a single class of MHC gene (most commonly class IIb), whereas selection can affect differentially the genetic diversity of both genes (Bryja et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation